(untitled) (Medico Legal Update, 2021)
Background: Even If Specific mechanisms are not completely understood, several studies highlighted Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) ability to alter vascular homeostasis. In the literature, multiple reports of microscopic pulmonary findings of vascular structures in patients deceased by or with SARS-Cov-2 infection are available. Nevertheless, the scientific literature lacks a systematic analysis of these findings. Methods: the authors realized a systematic review of the literature in order to identify common microscopic patterns representative of pulmonary vascular damage: useful data for pathologists in clinical and forensic settings. The research yielded 23 articles (79 total cases). Quali/ quantitative analysis was carried out. Conclusion: the review allowed to identify vascular thrombosis (especially in lesser caliber vessels) as common microscopic pattern. The recurrence of this pattern was confirmed by scientific literature data which demonstrate SARS-CoV-2 ability to interfere with coagulation cascade. Other meaningful microscopic findings were also discussed, even if their low frequency in study population did not allow to define them as common